Reading and Writing Successfully in College A Guide for Students - Lynne, Patricia (Open textbook library., 2023)
This textbook provides students with guidelines for understanding writing tasks as intellectual work using Bloom’s Taxonomy and for treating the writing process as a set of variable activities that move along a trajectory from idea or assignment to a finished product. The book also includes chapters on strengthening reading strategies and on finding, evaluating, and using sources effectively.